Study On Fatigue Damage Of Concrete Beams With Variable Notched Depth Using Acoustic Emission Technique - Kudus, Sakhiah Abdul (2014)
Concrete structure is the main materials used in constructions including the major and minor structure such as bridges, airports, highways pavements and offshore structure where this structures are subjected to the fatigue load. Concrete structure study on fatigue damaged by utilizing non-destructive testing (NDT) on concrete structure has been widely explored nowadays. Acoustic emission (AE) is one of the powerful NDT tool used for evaluating the damage occurrence in concrete structure. The present study emphasised on the using of AE in Structure Health Monitoring (SHM), on the notched beam samples undergoing fatigue loading. The main interest of this study was to investigate the capability of AE in quantifying the damage level of variable notch to depth ratios of concrete specimens which were subjected to fatigue loading. The four types of plain concrete beams with the same dimensions (100 x 200 x 600mm) but different notch to depth ratios was tested. A total of sixteen samples were tested under variables and increasing amplitudes of cyclic loading in closed loop servo-controlled hydraulic machine. The studied samples were tested in three points bending setup under monotonic and fatigue cyclic loading with each type of the notched beams contained seven beams; three beams for monotonic loading and four beams for fatigue cyclic loading. In order to detect and to collect the AE data, Micro-SAMOS (μ-SAMOS) digital AE system and R6I sensor type were used while data analyses were carried out using AEwin software. In addition, the b-value, the Ib-value, severity analysis and intensity analysis methods were applied to quantify the fatigue damage level of the notched beams undergoing fatigue loading. The AE technique was successfully used to determine fatigue damage mechanism and to classify the damage level occurrence during an increasing cyclic loading on notched concrete beams.